2004
DOI: 10.1074/jbc.m407604200
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Spectropotentiometric Characterization of Escherichia coli NrfB, a Decaheme Homodimer That Transfers Electrons to the Decaheme Periplasmic Nitrite Reductase Complex

Abstract: Escherichia coli can reduce nitrite to ammonium via a 120-kDa decaheme homodimeric periplasmic nitrite reductase (NrfA) complex. Recent structure-based spectropotentiometric studies are shedding light on the catalytic mechanism of NrfA; however, electron input into the enzyme has not been addressed biochemically. This study reports the first purification of NrfB, a novel 20-kDa pentaheme c-type cytochrome encoded by the nrfB gene that follows the nrfA gene in many bacterial nrf operons. Analyses by gel filtrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…In NrfA proteins that interact with NrfB, there is also a conserved lysine. However, this residue should not be involved in NrfB haem ligation, as all the haems of this cytochrome are known to be bis‐histidinyl coordinated (Clarke et al , 2004). Moreover, NrfA and NrfB proteins form a transient complex.…”
Section: Resultsmentioning
confidence: 99%
“…In NrfA proteins that interact with NrfB, there is also a conserved lysine. However, this residue should not be involved in NrfB haem ligation, as all the haems of this cytochrome are known to be bis‐histidinyl coordinated (Clarke et al , 2004). Moreover, NrfA and NrfB proteins form a transient complex.…”
Section: Resultsmentioning
confidence: 99%
“…At present, despite extensive efforts, the structure of MtrC is not known; however, primary structure analysis suggests that it, and also periplasmic decaheme MtrA [10], encodes two approximately 150 amino acid pentaheme modules with similarity to the pentaheme NrfB, an approximately 150 amino acid pentaheme periplasmic electron transport cytochrome widely involved in nitrite respiratory systems. All five hemes within NrfB are bishistidine-coordinated and it exhibits thermodynamic activity over a similar potential domain to MtrC [42].…”
Section: Discussionmentioning
confidence: 99%
“…As has also been proposed for the iron sulfur proteins encoded by the sirC and mccC genes from S. oneidensis MR-1 and W. succinogenes, respectively, E. coli NrfC couples instead to a c-type cytochrome protein, NrfB (17,21,43). In E. coli, NrfD, via the iron sulfur protein NrfC, has been proposed to reduce the pentaheme c-type cytochrome NrfB via a putative NrfAB (20-heme) heterotetrameric complex in vivo (5,6). Interestingly, Clarke et al showed that a truncation of an N-terminal MtrA polypeptide, which shares significant homology and similar heme organization to NrfB from E. coli, forms a mature c-type cytochrome, supporting the idea that larger cytochromes may be modular extensions of smaller ones (7).…”
Section: Discussionmentioning
confidence: 99%